Appropriate therapy for type 2 diabetes mellitus in view of pancreatic β‐cell glucose toxicity: "the earlier, the better". (27th October 2015) - Kaneto, Hideaki; Matsuoka, Taka‐aki; Kimura, Tomohiko; Obata, Atsushi; Shimoda, Masashi; Kamei, Shinji; Mune, Tomoatsu; Kaku, Kohei
Abstract: Pancreatic β‐cells secrete insulin when blood glucose levels become high; however, when β‐cells are chronically exposed to hyperglycemia, β‐cell function gradually deteriorates, which is known as β‐cell glucose toxicity. In the diabetic state, nuclear expression of the pancreatic transcription factors pancreatic and duodenal homeobox 1 (PDX‐1) and v‐Maf musculoaponeurotic fibrosarcoma oncogene family, protein A (MafA) is decreased. In addition, incretin receptor expression in β‐cells is decreased, which is likely involved in the impairment of incretin effects in diabetes. Clinically, it is important to select appropriate therapy for type 2 diabetes mellitus (T2DM) so that β‐cell function can be preserved. In addition, when appropriate pharmacological interventions against β‐cell glucose toxicity are started at the early stages of diabetes, β‐cell function is substantially restored, which is not observed if treatment is started at advanced stages. These observations indicate that it is likely that downregulation of pancreatic transcription factors and/or incretin receptors is involved in β‐cell dysfunction observed in T2DM and it is very important to start appropriate pharmacological intervention against β‐cell glucose toxicity in the early stages of diabetes.